1985
DOI: 10.3109/00016488509182253
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Different Methods for Assessing the ‘Intensity’ of Tinnitus

Abstract: Questions are raised about the technical and psychological interpretation of loudness match measures in the assessment of tinnitus "intensity". The effect of hearing threshold on loudness matches expressed in sensation level (SL) was investigated by selecting subjects with different degrees of hearing loss. The loudness match expressed in SL was found to be a function of threshold. Correlations were then determined between psychological scales of tinnitus complaint (reported loudness, distress, intrusiveness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
5

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 5 publications
1
24
0
5
Order By: Relevance
“…depression and anxiety), but also to poor concentration, irritability, and locus of control. (Attias et al, 1995;Baskill et al, 1991;Coles et al, 1991;Collet et al, 1990;Erlandsson et al, 1992;Erlandsson & Holgers, 2001;Gerber et al, 1985/86;Halford 1991;Hallam et al, 1985;Hallberg & Erlandsson, 1993;Holgers et al, 2000;Kuk et al, 1990;Newman et al, 1994;Newman et al, 1998;Wilson et al, 1991).…”
Section: Sumariomentioning
confidence: 91%
“…depression and anxiety), but also to poor concentration, irritability, and locus of control. (Attias et al, 1995;Baskill et al, 1991;Coles et al, 1991;Collet et al, 1990;Erlandsson et al, 1992;Erlandsson & Holgers, 2001;Gerber et al, 1985/86;Halford 1991;Hallam et al, 1985;Hallberg & Erlandsson, 1993;Holgers et al, 2000;Kuk et al, 1990;Newman et al, 1994;Newman et al, 1998;Wilson et al, 1991).…”
Section: Sumariomentioning
confidence: 91%
“…The differentiation between loudness and annoyance has also been suggested by studies showing that only weak to moderate correlations exist between audiologically matched loudness and subjective distress [Meikle et al, 1984;Hallam et al, 1985;Folmer et al, 1999;Henry and Meikle, 2000]. Andersson et al [1999] used the Klockhoff and Lindblom system and found that grades II and III were predictable from a cluster of variables including tinnitus pitch, minimal masking level, avoidance of situations because of tinnitus and tinnitus tolerance at present in relation to onset.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to investigate the causative factors of tinnitus. [3][4][5][6][7][8][9][10][11][12][13][14] Some have shown that the limitations due to tinnitus depend on primary psychological factors, such as difficulties in dealing with the problem, 8,12,[15][16][17] altered humor (depression and anxiety), low concentration, irritability, loss of control, 18 and a variety of psychiatric conditions and specific personality traits. 12,[15][16][17]19 Contrary to what was commonly thought, Jastreboff and Hazell 2 demonstrated that there are no psychoacoustic differences of tinnitus (intensity, frequency and minimum suppression level) among patients with tinnitus that suffer and those that do not.…”
Section: Introductionmentioning
confidence: 99%